Relações parentais e a prevenção ao uso de drogas: contribuição piagetiana - Freiria, Marcos Henriques da [UNESP] (2017)
In this dissertation, we present the results of a Master's Degree in Education which objective was to verify the influence of the parental educational style in the prevention of psychoactive substances use by adolescents. Also, it was investigated whether there was an association between the type of respect (unilateral and mutual) and prevention of drug use, based on the moral psychology of Jean Piaget. The case study was developed in a public school located in the periphery of a medium-sized city of the western region of São Paulo. The subjects were 33 students of both sexes, enrolled in the 9th year of elementary education, aged between 13 and 17 years and socioeconomic level C, according to criteria defined by the Brazilian Association of Research Companies. Through a questionnaire and interviews based on the Piagetian Clinical Method, it was possible to verify that there isn’t a relationship between parental educational styles and use of psychoactive substances. However, there seems to be such relation regarding to the nature of the drugs consumed, because the subjects who were submitted to the authoritative style made use of the lawful ones. It was possible to verify the prevalence of unilateral respect between parents and children and the existence of a relationship between use of psychoactive substances, gender, family structure, religious practice and level of information about drugs. Considering these aspects, the conclusion is that the work regarding the prevention of drug use should consider the kind of respect established between parents and children.